2018
DOI: 10.1016/j.cemconres.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of hydration of MgO-hydromagnesite blends

Abstract: The hydration of reactive periclase (MgO) in the presence of hydromagnesite (Mg 5 (CO 3 ) 4 (OH) 2 ·4H 2 O) was investigated by a variety of physical and chemical techniques. Hydration of pure MgO-water mixtures gave very weak pastes of brucite (Mg(OH) 2 ), but hydration of MgO-hydromagnesite blends gave pastes which set quickly and gave compressive strengths of potential interest for construction applications. The strengths of the blends increased with hydration time at least up to 28days, and were not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 26 publications
8
67
1
Order By: Relevance
“…After 95 days of hydration, there were two major differences between cement and CWA in the hydrated samples ( Figure 9 b); the broad band at about 3400 cm −1 corresponding to the O−H stretching vibrations (v1 and v3) in the water molecules was much more pronounced in CWA than in cement, confirming that CWA retains water [ 46 ]. The band in the range 1420–1480 cm −1 is attributed to CO 3 2− /HCO 3 − [ 45 ], confirming the formation of more carbonates in CWA. These carbonates could fill the cracks or voids and consequently contribute to a denser structure and less water penetration.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…After 95 days of hydration, there were two major differences between cement and CWA in the hydrated samples ( Figure 9 b); the broad band at about 3400 cm −1 corresponding to the O−H stretching vibrations (v1 and v3) in the water molecules was much more pronounced in CWA than in cement, confirming that CWA retains water [ 46 ]. The band in the range 1420–1480 cm −1 is attributed to CO 3 2− /HCO 3 − [ 45 ], confirming the formation of more carbonates in CWA. These carbonates could fill the cracks or voids and consequently contribute to a denser structure and less water penetration.…”
Section: Resultsmentioning
confidence: 95%
“…ATR-FTIR analyses were also performed on powdered material (cement and CWA) and on the hydrated samples at 95 days of age ( Figure 9 ). All bands identified by FTIR ( Figure 9 a) are those commonly found in cements, and the only significant difference between CEM and CWA is a band at 3700 cm −1 attributed to Mg(OH) 2 [ 45 ]. Some carbonates could also be present, e.g., a single asymmetric stretching band observed between 1450 and 1400 cm −1 could be attributed to MgCO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of bands were observed in the MgO power, which were also apparent in the prepared samples, along with additional bands. The band at ~3700 cm -1 was associated with the anti-symmetrical stretching of O-H bonds, referring to the formation of brucite [47][48][49]. Similarly, the presence of brucite was also linked with the small band at ~3650 cm -1 , which was attributed to the free O-H vibration [47][48][49][50].…”
Section: Ftir Analysismentioning
confidence: 99%
“…A few small bands were observed in the region from 1380 to 1450 cm -1 , which could be ascribed to the formation of different carbonate phases. The peak profile and band width between this region could show variations, depending on the type of carbonates [47][48][49][50]. The band at ~1120 cm -1 was due to the symmetrical stretching of the CO3 2ion [47,53,54], whereas the band at ~1015 cm -1 occurred due to the symmetrical stretching of CO3 2in the form of magnesium carbonate [47].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Kuenzel et al [27] studied the influence of hydromagnesite on MgO hydration and found that hydromagnesite reacted with MgO to form artinite, with a strength of 24.6 MPa. The reaction is as follows:…”
Section: Introductionmentioning
confidence: 99%